Optimizing the Development of children with mental retardation by the Gardening Challenge Program - Rosmaharani, Shanti; Noviana , I’in; Rodiyah, Rodiyah; Fitri, Luthfi Nazillatul; Magfiroh, Gita; Amirta, Adinda Zakia Putri; Aditya, Arya Rakha; Prasetyo, Achmad Yogi; Andrian, Bela Kurnia (Lembaga Dongan Dosen, 2024)
Mental retardation is a state of stopped or incomplete mental development which is characterized by disturbances during development, thus affecting the overall level of intelligence. Gardening therapy of the Gardening Challenge Program can be a solution to improve student’s health and can be a learning tool for school development. This Community Service aims to improve student health and increase creative activities in education. This activity is included in the Community Partnership Program scheme which is funded by the Ministry of Education and Culture. The methods used in this program are health education, family psychoeducation and gardening training which are packaged in the Gardening Challenge Program. The first activity is health education about sexual violence. This education explains the importance of awareness of preventing sexual violence, especially for students with special needs. The second activity is family psychoeducation. The Family psychoeducation is a method that provides education to families about caring for children with mental retardation. This family psychoeducation was carried out in 2 sessions. The next activity is the Gardening Challenge Program, namely training in plant breeding and cultivation and making demonstration plots. This activity went smoothly and was attended by 40 students. The results of this activity are increased development of children's growth and development, increased family capabilities in caring for mentally retarded children and increased school activities by forming demonstration plots which can be used as an educational tool. Students, families and the school responded well and enthusiastically to the benefits provided by this community service